Non-isothermal study of the devitrification kinetics of fluoroindate glasses - Costa, Bill J.; Poulain, Marcel; Messaddeq, Younes [UNESP]; Ribeiro, Sidney José Lima [UNESP] (Elsevier, 2000)
The understanding of the kinetics of devitrification of a glass is important for anticipating its stability in a particular purpose, such as fiber-drawing processes. The crystallization kinetics of (BaF2)16(ZnF2)20(SrF 2)20(NaF)2 (GaF3)5(InF3)36(GdF 3)1 glass prepared by quenching were studied by differential scanning calorimetry (DSC). Avrami's exponent (n) obtained by a non-isothermal method was 4.3 for a solid and 2.4 for a powdered sample. According to the classical interpretation of n, these magnitudes correspond to an interface-controlled crystal growth and a diffusion-controlled crystal growth, respectively. The activation energies for crystallization (E) was 62 ± 1 kJ/mol for solid glass and 245 ± 2 kJ/mol for powdered glass. These results are discussed in terms of glass particle size. © 2000 Elsevier Science B.V. All rights reserved.